P125 New horizons in malignant transformation of endometriosis, a retrospective study on all cases in northern ireland. (1st November 2019) - Graham, M; Nagar, H; McComiskey, M; Dobbs, S; Harley, I; Hunter, D; McCluggage, G; Craig, E
Abstract : Introduction/Background: This study aims to determine the prevalence, risk factors and outcomes of ovarian endometrioid carcinoma (EC) and clear cell carcinoma (CCC) and identify patients at risk of malignant transformation. Methodology: 161 patients were identified using histopathology records from March 2011 to June 2018. Patient information was collected using an electronic database. All patients had multi-disciplinary team discussion and dedicated histopathological review. Results: 95 patients had EC (59.%), 55 patients had CCC (34.1%) and 8 patients had synchronous EC and CCC (4.9%). The mean age of presentation was 57 with the majority of patients (74.5%) presenting over the age of 50. 14 patients had a known clinical history of endometriosis. The mean Ca125 was 514 (Range 9-16042, 95% CI 764.1) with the nearly all patients (81.3%) having a raised Ca125. At time of presentation 129 patients had a pelvic mass ≥10cm. The most common presenting complaint was pressure symptoms/abdominal mass (59–36.6%) or post-menopausal bleeding (24–4.9%). 69.5% patients had early disease (Stage 1). 102 patients had endometriosis on histopathology (63.7%). 101 patients had adjutant treatment (64.7%) and 120 (74.5%) patients were still alive as per March 2019 with an Overall Survival of 48 months for both EC and CCC subtypes. Conclusion: There is an average of 22 cases of ovarian EC or CCC each year in Northern Ireland. The majority of patients present after the age of 50 with pressure symptoms and a pelvic mass ≥10cm. We discuss preoperative risk factors suggestive of malignant transformation and outcomes following treatment. This study has highlighted the need for careful long- term observation of a patient with endometriomata to detect possible malignant change, leading to development of a multi- disciplinary strategy for better prevention, early detection, specific diagnosis and treatment targeting molecular pathogenesis to understand the mechanisms of endometriosis- associated ovarian cancer in Northern Ireland. Disclosure: Nothing to disclose.